PVC (polyvinyl chloride) composition and application thereof in preparation of high-compression-resistance and anti-electromagnetic-interference PVC electrical conduit
By adding calcium carbonate, fly ash glass microbeads and carbon nanotubes to the PVC resin, a PVC composition was prepared, which solved the problem that existing PVC pipes were difficult to achieve high compressive resistance, impact resistance, bending toughness and electromagnetic interference at the same time, and achieved a balance between high compressive resistance, electromagnetic interference resistance and good mechanical properties of PVC electrical casings.
Patent Information
- Application Number
- CN202411406394.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
It is difficult for existing PVC pipes to achieve high compressive resistance, impact resistance, bending toughness and electromagnetic interference resistance at the same time.
By adding calcium carbonate, fly ash glass microbeads and carbon nanotubes to the PVC resin, a PVC composition can be prepared. This composition can improve the compressive resistance and electromagnetic interference resistance of the electrical casing, while maintaining good impact toughness and bending toughness.
The high compressive resistance, electromagnetic interference resistance and good mechanical properties of PVC electrical casing are achieved, and the comprehensive performance of electrical casing is improved.
Smart Images

Figure BDA0005076709390000051 
Figure BDA0005076709390000061 
Figure BDA0005076709390000062
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of plastic pipes, and in particular relates to a PVC composition and an application thereof in preparing a high-pressure and electromagnetic interference-resistant PVC electrical casing. Background Art
[0002] With the rapid development of the communications industry, computer industry and home improvement market, electronic appliances and radio communications are widely used, and electrical conduits are needed to protect wires. When wires or communication cables are installed crosswise or in parallel, interference magnetic fields will be formed around the wires through which current passes, affecting the normal operation and signal transmission of various electronic equipment, threatening the information security of communication equipment, and causing great harm to human health. Therefore, electrical conduits with anti-electromagnetic interference effects are gradually being researched and developed.
[0003] On the other hand, with the rapid development of modern construction industry, the threading pipe is usually embedded in reinforced concrete or buried under the floor, which requires the threading pipe to have a certain ability to resist flattening. The relevant industry standards require plastic materials to have high modulus, certain impact toughness and bending toughness. However, it is difficult to improve the modulus and toughness of plastic materials at the same time.
[0004] The prior art discloses a flame-retardant electromagnetic shielding polyvinyl chloride material and a production method and an electrical conduit, which uses stainless steel metal fibers to fill the PVC material to obtain a PVC electrical conduit with electromagnetic shielding effect. However, the use of metal fibers or metal powders to fill the PVC material is less used due to the poor compatibility between metal and plastic, the poor fluidity of the material, and the difficulty in processing. In addition, the unqualified products produced are difficult to recycle and reuse. In addition, the prior art discloses a low-temperature toughened rigid polyvinyl chloride electrical conduit, but the electromagnetic resistance of the electrical conduit is not tested, and the impact resistance and bending resistance need to be improved.
[0005] Therefore, developing a PVC composition to prepare a PVC electrical conduit with high compressive resistance, anti-electromagnetic interference performance, and good mechanical properties has important research significance and application value. Summary of the invention
[0006] In order to solve the challenge that PVC pipes in the prior art are difficult to achieve good compression resistance, impact resistance, bending toughness, and anti-electromagnetic interference, the primary purpose of the present invention is to provide a PVC composition, including PVC resin, calcium carbonate, fly ash glass beads, carbon nanotubes, and a heat stabilizer.
[0007] Another object of the present invention is to provide a method for preparing the above PVC composition.
[0008] Another object of the present invention is to provide the use of the above PVC composition in the preparation of electrical conduits for communication or power transmission.
[0009] Another object of the present invention is to provide a PVC electrical conduit made from the above PVC composition.
[0010] Another object of the present invention is to provide a method for preparing the above-mentioned PVC electrical conduit.
[0011] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0012] The present invention protects a PVC composition comprising the following components in parts by weight:
[0013] 100 parts of PVC resin, 10-35 parts of calcium carbonate, 2-12 parts of fly ash glass microbeads, 2-10 parts of carbon nanotubes, and 3-6 parts of heat stabilizer.
[0014] The present invention develops a PVC composition having high compressive strength, anti-electromagnetic interference performance and good mechanical properties by adding calcium carbonate, fly ash glass microbeads and carbon nanotubes to PVC resin. Among them, calcium carbonate can improve the impact performance and bending performance of electrical casing; fly ash glass microbeads can effectively improve the bending modulus of PVC resin, thereby improving the compressive strength of electrical casing, and the price is lower than that of ordinary glass microbeads, which can effectively reduce the cost; carbon nanotubes are an excellent conductive modifier, and a small amount of addition can make plastics conductive, thereby achieving anti-electromagnetic interference, and will not reduce the mechanical properties of PVC resin.
[0015] Calcium carbonate, fly ash glass microbeads, and carbon nanotubes are all fillers for PVC resin. The addition of the above three fillers can increase the rigidity of PVC, improve the modulus, and enhance the compressive performance of the electrical conduit; but if too much filler is added, the impact performance and bending performance of the electrical conduit will be significantly reduced, so a certain addition ratio needs to be met to achieve a balance. The addition of carbon nanotubes can improve the anti-electromagnetic interference performance of the electrical conduit. The more added, the better the anti-electromagnetic interference performance, but adding too much will cause the impact performance and bending performance of the electrical conduit to be significantly reduced. Therefore, the present invention limits the addition ratio of each component so that the prepared electrical conduit has both high compressive resistance and anti-electromagnetic interference performance, while maintaining good impact toughness and bending toughness.
[0016] Preferably, the PVC composition comprises the following components in parts by weight:
[0017] 100 parts of PVC resin, 20 parts of calcium carbonate, 10 parts of fly ash glass microspheres, 8 parts of carbon nanotubes, and 4 parts of heat stabilizer.
[0018] Preferably, the particle size of the fly ash glass beads is 5 to 25 μm.
[0019] The particle size of fly ash glass beads is 5 to 25 μm. The spherical particles determine that they have a minimum specific surface area and low oil absorption rate. The amount of resin used can be greatly reduced during use. Even with a high addition amount, the viscosity will not increase much, which greatly improves the production operating conditions and can increase production efficiency by 10% to 20%.
[0020] More preferably, the particle size of the fly ash glass microbeads is 12.5 to 17.5 μm, more preferably 15 μm.
[0021] Preferably, the calcium carbonate is conventional calcium carbonate or nano calcium carbonate. More preferably, the particle size of the nano calcium carbonate is 20 to 100 nm.
[0022] Nano calcium carbonate has a nanometer particle size. Due to its small particle size, it is more densely packed and is less likely to cut the molecular chain than ordinary calcium carbonate. It can further improve the impact performance and bending performance of electrical conduits.
[0023] Preferably, the carbon nanotube is at least one of single-walled carbon nanotube, double-walled carbon nanotube or multi-walled carbon nanotube.
[0024] More preferably, the carbon nanotubes are multi-walled carbon nanotubes.
[0025] Single-walled carbon nanotubes are very expensive due to the difficult manufacturing process and very low output, while multi-walled carbon nanotubes are cheaper and can be used as conductive modifiers to effectively reduce the manufacturing cost of electromagnetic interference-resistant PVC electrical conduits.
[0026] Preferably, the carbon nanotubes are titanate coupled carbon nanotubes.
[0027] The use of titanate coupling agent can reduce the agglomeration of carbon nanotubes, improve the compatibility of inorganic fillers with resins, make the fillers more evenly dispersed in the resin, reduce melt viscosity, improve processing performance, and improve the impact strength, tensile strength, flexibility and other mechanical properties of the products.
[0028] More preferably, the titanate is at least one of isopropyl tristearate titanate, isopropoxy triisostearate acyloxy titanate or isopropyl dioleate acyloxy titanate.
[0029] More preferably, the method for preparing titanate coupled carbon nanotubes comprises the following steps:
[0030] The titanate coupling agent and the carbon nanotubes were mixed and stirred for 0.5 h using a small mixer.
[0031] Preferably, the viscosity of the PVC resin is 118-107 mL / g, and the test method is GB / T 3401.
[0032] Preferably, the multi-walled carbon nanotube has a length of 5 to 30 μm and a diameter of 2 to 30 nm, contains multiple layers of graphene sheets, the number of layers is 2 to 5, and the interlayer spacing is 0.34 nm.
[0033] Preferably, the heat stabilizer is a calcium zinc stabilizer.
[0034] Preferably, the PVC composition further comprises at least one of an impact-resistant agent, a processing aid or a lubricant.
[0035] More preferably, the anti-impact agent is chlorinated polyethylene.
[0036] More preferably, the processing aid is ACR.
[0037] More preferably, the lubricant is polyethylene wax.
[0038] The present invention also provides a method for preparing the PVC composition. The PVC composition is obtained by uniformly mixing the components and performing melt extrusion.
[0039] The invention also provides a PVC electrical casing, which is prepared from the composition.
[0040] The present invention also provides a method for preparing a PVC electrical casing, comprising the following steps:
[0041] The above components are mixed evenly, melt-extruded through a screw extruder, and cooled and shaped to obtain the PVC electrical conduit.
[0042] Preferably, the barrel temperature of the screw extruder is 140-190°C, and the die temperature is 140-220°C.
[0043] The use of the above PVC composition in the preparation of electrical conduits for communication or power transmission also falls within the protection scope of the present invention.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] The calcium carbonate, fly ash glass microbeads and carbon nanotubes in the PVC composition provided by the present invention meet the addition ratio, which can improve the mechanical properties of PVC while achieving a high balance between the compression resistance and impact bending toughness of the corresponding electrical casing, and has excellent anti-electromagnetic interference performance;
[0046] The PVC composition provided by the invention utilizes fly ash glass microbeads with a particle size of 5 to 25 μm to enhance the bending modulus and compression resistance of the PVC electrical casing and has low cost. DETAILED DESCRIPTION
[0047] The present invention is further described below in conjunction with examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually carried out according to conventional conditions in the art or according to the conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets. Any non-substantial changes and substitutions made by those skilled in the art on the basis of the present invention belong to the scope of protection claimed by the present invention.
[0048] Some of the reagents selected in the embodiments and comparative examples of the present invention are described as follows:
[0049] PVC resin 1: Jin Yuyuan type V resin powder, Jin Yuyuan type V resin powder viscosity 110mL / g, test method GB / T3401;
[0050] PVC resin 2: Xinjiang Zhongtai SG5 viscosity number 112mL / g, test method GB / T 3401;
[0051] Calcium carbonate 1#, Huaming SPSL, particle size 60-90nm;
[0052] Calcium carbonate 2#: Guilin Jinshan New Materials, JD200, particle size D99<8.5μm;
[0053] Fly ash glass microspheres 1#: Xingtai Jiahui Insulation Materials Co., Ltd., particle size is 15μm;
[0054] Fly ash glass microspheres 2#: particle size is 5μm;
[0055] Fly ash glass microbeads 3#: particle size is 25μm;
[0056] Conductive modifier-carbon nanotube 1#: multi-walled carbon nanotube, Deco CNT104, diameter 10-20 nm, length 10-30 μm, treated with titanate coupling agent;
[0057] Carbon nanotube 2#: multi-walled carbon nanotube, Deco CNT104, diameter 10-20 nm, length 10-30 μm, not treated with titanate coupling agent;
[0058] Calcium zinc stabilizer: Jinchangshu 316Y;
[0059] Processing aids: Riko LPA-40, ACR;
[0060] Anti-impact agent: Nikko 135A chlorinated polyethylene;
[0061] Lubricant: polyethylene wax;
[0062] Titanate: isopropyl titanate tristearate;
[0063] Fly ash: commercially available;
[0064] Ordinary glass beads: Huaxing C20.
[0065] The titanate coupled carbon nanotubes used in the embodiments and comparative examples of the present invention are prepared by the following process:
[0066] The titanate coupling agent and the carbon nanotubes were mixed and stirred for 0.5 h using a small mixer.
[0067] The PVC electrical conduits of the embodiments and comparative examples of the present invention are prepared by the following process:
[0068] S1. Put polyvinyl chloride resin, nano calcium carbonate or ordinary calcium carbonate, multi-walled carbon nanotubes, fly ash glass beads or fly ash, calcium zinc heat stabilizer, impact agent chlorinated polyvinyl chloride, processing aid ACR, lubricant polyethylene wax, put into a mixer and mix well to obtain a mixed ingredient;
[0069] S2. The premix is melt-extruded through a screw extruder, cooled and shaped to obtain a high-pressure and anti-electromagnetic interference PVC electrical conduit. The barrel temperature of the screw extruder is 160°C and the die temperature is 180°C.
[0070] The performance test methods and standards of the PVC electrical conduits of the embodiments and comparative examples of the present invention are as follows:
[0071] (1) -15℃ impact toughness: JG / T 3050 Clause 6.5;
[0072] (2) -15℃ flexural toughness: JG / T 3050 Clause 6.6;
[0073] (3) Flexural modulus (MPa): GB / T 9341;
[0074] (4) Electromagnetic shielding effect (dB): GB / T 30142;
[0075] (5) Compression resistance (%): JG / T3050 Clause 6.4.
[0076] Examples 1 to 8
[0077] This embodiment provides a series of PVC electrical conduits, and the weight proportions of the components in the formula are shown in Table 1.
[0078] Table 1 Examples 1 to 8 formulations (parts)
[0079]
[0080]
[0081] Comparative Examples 1 to 8
[0082] This comparative example provides a series of PVC electrical conduits, and the components in the formula are shown in Table 2.
[0083] Table 2 Formulas of Comparative Examples 1 to 8 (parts)
[0084]
[0085] The performance test results of the PVC electrical conduits in the embodiments and comparative examples according to the above-mentioned method are shown in Table 3.
[0086] Table 3 Performance test results of various embodiments and comparative examples
[0087]
[0088] The data in Table 3 show that the PVC electrical conduits prepared in Examples 1 to 8 of the present invention have the characteristics of high pressure resistance and anti-electromagnetic interference performance, among which Example 1 has the best comprehensive performance.
[0089] According to the data in Table 3, in Comparative Example 1, no calcium carbonate was added, and the corresponding PVC electrical conduit had a compressive resistance of 61%, and the flexural modulus was greatly reduced; in Comparative Example 2, no fly ash glass beads were added, which proved that the compressive resistance decreased, and the electromagnetic shielding effect remained at 70dB; in Comparative Example 3, no multi-walled carbon nanotubes were added, and the electromagnetic shielding effect dropped to 5dB, which was significantly lower than that in the embodiment, indicating that the multi-walled carbon nanotubes mainly affected the electromagnetic shielding effect; in Comparative Examples 4 and 5, the ratio of calcium carbonate to glass beads was out of the range, which proved that when the amount of calcium carbonate was increased, the compressive resistance was improved to 15%, and the electromagnetic shielding effect was 72dB, but the impact Toughness and bending toughness decreased. When the amount of fly ash glass beads was reduced, the compressive performance was improved, and the electromagnetic shielding effect was 71dB, but the impact toughness decreased. Comparative Example 6 used fly ash instead of fly ash glass beads, which proved that the compressive resistance, impact toughness and bending toughness were significantly reduced when using fly ash. Comparative Example 7 used ordinary glass beads instead of fly ash glass beads, the compressive performance was reduced, and the impact toughness decreased. Comparative Example 8 added carbon nanotubes beyond the range. Although the electromagnetic shielding effect was 91dB, the impact toughness and bending toughness were greatly reduced, indicating that the amount added must be within the range.
[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A PVC composition, characterized in that: The composition comprises the following components in parts by weight: 100 parts of PVC resin, 10-35 parts of calcium carbonate, 2-12 parts of fly ash glass microbeads, 2-10 parts of carbon nanotubes, and 3-6 parts of heat stabilizer.
2. The PVC composition according to claim 1, characterized in that: The particle size of the fly ash glass microbeads is 5 to 25 μm.
3. The PVC composition according to claim 1, characterized in that: At least one of an anti-impact agent, a processing aid or a lubricant is also included.
4. The PVC composition according to claim 1, characterized in that: The carbon nanotube is at least one of a single-walled carbon nanotube, a double-walled carbon nanotube or a multi-walled carbon nanotube.
5. The PVC composition according to claim 1, characterized in that: The carbon nanotubes are titanate coupled carbon nanotubes.
6. The PVC composition according to claim 5, characterized in that: The titanate is at least one of isopropyl tristearate titanate, isopropoxy triisostearate acyloxy titanate or isopropyl dioleate acyloxy titanate.
7. The method for preparing the PVC composition according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: uniformly mixing the above components and melt-extruding the components to obtain the PVC composition.
8. Use of the PVC composition according to any one of claims 1 to 6 in the preparation of electrical conduits for communication or power transmission.
9. A PVC electrical conduit made from the PVC composition according to any one of claims 1 to 6.
10. The method for preparing the PVC electrical casing according to claim 9, characterized in that: The components of the PVC composition according to any one of claims 1 to 6 are mixed uniformly, melt-extruded through a screw extruder, and cooled and shaped to obtain the PVC electrical conduit.
Citation Information
Patent Citations
Ultra-clean antistatic resin composition, preparing method thereof, product containing the same and application thereof
CN101016406A
Polyvinyl chloride tube for anti-electromagnetic interference, and preparation method of tube
CN106832666A
High-strength composite electric power tube and preparation process thereof
CN113583365A
PVC nanocomposite manufacturing technology and applications
US20080194736A1